Seleksi in Vitro Genotipe Mutan (M3) Kipas Putih untuk Toleransi terhadap Kekeringan - Zuyasna Zuyasna; Chairunnas Chairunnas; Zuraida Zuraida (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Syiah Kuala, 2017)
Selection of 3rd generation soybean mutants (M3) of Kipas Putih has been selected for tolerance of drought stress. The research was conducted at the Tissue Culture Laboratory of Faculty of Agriculture, Syiah Kuala University, Darussalam - Banda Aceh. Gamma ray irradiation was performed at Puslitbang Teknologi Isotop dan Radiasi BATAN, Pasar Jumat Jakarta. Seed of Varietas Wilis and Dering soy bean was used as control for drought tolerant and Kipas Putih was used as original variety. Selection was performed in vitro by using 20% Polyethylene Glycol (PEG). The results showed there were 8 genotype mutants categorized as tolerant to drought stress, ie KP100-26, KP100-28, KP200-31A, KP200-38, KP200-51, KP200-62, KP300-34, and KP300-47. Eleven mutan genotypes were categorized as medium tolerant and six genotypes were sensitive to drought. Selection of M4 generation selected lines are needed to find the drought tolerant and high-yielding mutant.